ROLE OF MICRO ORGANISMS IN TEMPLE WASTES MANAGEMENT ASSISTED BY EUDRILLUS EUGENIA - Arumugam, Karthika; Venkatachalam, Anbuarasi; Muthunarayanan, Vasanthy; Ganesan, Seetha Devi; Vivek, Swabna; Sugumar, Susila (Malaysian Journal of Science, 2014)
The increasing solid waste generation rates and their high collection cost were some of the major problems in India. This paper deals with the effective management of Temple wastes. The temple waste consists of coconut, leaves, flowers, fruits etc which are of biodegradable in nature.It also includes milk products, grains and water, which could facilitate the growth of microorganisms. Such biodegradable temple wastes are released as such into the water bodies (or) dumped haphazardly which causes environmental pollution. Recycling of such temple waste is performed through vermitechnology employing Eisenia fetida. Three types of waste were prepared. They were as follows: TA (control), TB (Temple waste+ Cow dung), TC (Temple waste+ Cowdung+ Microbial inoculum) in different proportions in the 1 kg capacity Reactor vessels. The physic chemical parameters like pH, Electrical Conductivity, Total Kjeldahl nitrogen, Total Organic Carbon, Total Organic Matter and Carbon-Nitrogen ratio and phosphorus were tested in the vermicompost. Bacterial strains isolated from vermicompost and identified and are used as an inoculum to check whether they could enhance the rate of degradation. The impact of the prepared vermicompost on chick pea seed germination was also studied. These studies showed a significant growth in terms of length and height of the plant with TC vermicompost when compared to TA and TB vermicompost. Thus, it is concluded that the vermicomposting supplemented with the bacterial cultures is comparatively efficient technology for the effective management of the temple waste in an eco friendly manner. Keywords: Vermicompost, Temple waste, Eisenia fetida, Chick pea.